Worship, Ritual, and Pentecostal Spirituality-as-Theology: A Rhythm that Connects our Hearts with God - Björkander, Martina (Brill, 2024)
"Vibrant worship music is part of the Charismatic liturgy all around the world, and has become in many ways the hallmark of Pentecostal-Charismatic Christianity. Despite its centrality, scholarly interest in the theological and ritual significance of worship for pentecostal spirituality has been sparse, not least in Africa. Combining rich theoretical and theological insight with an in-depth case study of worship practices in Nairobi, Kenya, this interdisciplinary study offers a significant contribution to knowledge and is bound to influence scholarly discussions for years to come. The book is a must-read for anyone interested in Pentecostal worship, ritual, and spirituality"--